A field investigation related to professional management - Barrezueta, Andrea Fernanda (Revista Minerva, 2020)
The perspective of the world of work is fundamentally expressed in the professional profile of human talent. This articulates the set of professional achievements that the technician can demonstrate in the various work situations typical of his occupational area, once he has completed the training process. In these achievements, the staff shows their competence to solve the problems of a complex, changing and uncertain work world and their ability to learn from the new situations they face. For the professional profile, it is made up of a series of tasks, behaviors, attitudes, competencies and related skills in an integrated set that aims to be configured as a “professional personality”. The professional profile is a fundamental reference at the present time, because it guides the management process by specifying the competencies that the staff must develop, it also constitutes the main source for the identification of the problematic situations that the collaborator faces in their daily actions. For the Profile. -Set of parameters (age, level of education, hobbies, etc.) that delimit the characteristics of a target group, of a set of population that has a certain behavior or of the members of a list or database.